Detection and restoration of cracked digitized paintings and manuscripts using image processing - a survey - Farajalla Ali, Nawafil Abdulwahab; Alshaikhli, Imad Fakhri Taha (IIUM Press, International Islamic University Malaysia, 2017)
The restoration of paintings and manuscripts is defined as the process of restoring old and damaged artworks and documents exhibiting cracks. Cracks are caused by three factors; aging, drying up of painting material, and mechanical. It is necessary that cultural heritages be restored to their original or a near-original state. To enhance the overall quality of the image, there are different techniques and methodologies that can be used for conservation and restoration. The main objective of this study is to analyse techniques and methodologies that have been developed for the detection, classification of small patterns, and restoration of cracks in digitized old painting and manuscripts. The purpose of this research is to present previous works on detection and restoration of cracks using image processing techniques and methodologies.